2015
DOI: 10.1002/2014jb011519
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of compacting porous lavas

Abstract: The highly transient nature of outgassing commonly observed at volcanoes is in part controlled by the permeability of lava domes and shallow conduits. Lava domes generally consist of a porous outer carapace surrounding a denser lava core with internal shear zones of variable porosity. Here we examine densification using uniaxial compression experiments on variably crystalline and porous rhyolitic dome lavas from the Taupo Volcanic Zone. Experiments were conducted at 900°C and an applied stress of 3 MPa to 60% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 95 publications
(168 reference statements)
2
47
0
Order By: Relevance
“…S-C fabric formation may also have led to compaction and porosity reduction in the magma perpendicular to the S plane, which would have increased its viscosity (cf. Ashwell et al, 2015;Kennedy et al, 2016). The orientation of the C plane parallel to the flow banding (and the contact) suggests that the S-C fabrics in the main body of the Sandfell laccolith are induced by the combined intrusive contact-perpendicular (compressive) stresses and flexural shear due to the inflation of the magma body causing σ 1 to be oriented 45-60 • to the contact.…”
Section: Discussion Deciphering Magma Flow In the Sandfell Laccolithmentioning
confidence: 99%
See 2 more Smart Citations
“…S-C fabric formation may also have led to compaction and porosity reduction in the magma perpendicular to the S plane, which would have increased its viscosity (cf. Ashwell et al, 2015;Kennedy et al, 2016). The orientation of the C plane parallel to the flow banding (and the contact) suggests that the S-C fabrics in the main body of the Sandfell laccolith are induced by the combined intrusive contact-perpendicular (compressive) stresses and flexural shear due to the inflation of the magma body causing σ 1 to be oriented 45-60 • to the contact.…”
Section: Discussion Deciphering Magma Flow In the Sandfell Laccolithmentioning
confidence: 99%
“…The low vesicle content in coherent fracture-poor rhyolite exposed in the lower parts of Sandfell and the overall small vesicle sizes in fractured rock suggest that the Sandfell rhyolite was quite impermeable and therefore could not have effectively been degassing due to the transport from source to emplacement location ( Figure 5G). However, Ashwell et al (2015) showed in experiments on rhyolitic dome lavas that the porosity of the lava decreased at a constant shear rate. Reducing the porosity in magma by compaction, pore collapse and/or degassing increases the magma viscosity (Ashwell et al, 2015;Heap et al, 2015;Kushnir et al, 2017).…”
Section: Syn-emplacement Fracturingmentioning
confidence: 99%
See 1 more Smart Citation
“…At volcanoes, the porous network comprises of vesicles and fractures that build the permeable network and which controls degassing (Ashwell et al, 2015). Porosity also controls the mechanical response of materials whereby their strength decreases and elasticity increases with porosity (e.g., Al-Harthi et al, 1999;Spieler et al, 2004;Paterson and Wong, 2005;Heap et al, 2014a,b).…”
Section: Introductionmentioning
confidence: 99%
“…3D imaging via conventional and synchrotron-based X-ray computed microtomography as well as neutron computed tomography offers the ability to image and quantify rock textures directly in 3D in unprecedented detail and references therein, Lavallée et al 2013, Arzilli et al 2016. Through 3D textural investigations we are able to view structures that are the result of strain localization [Wright and Wimberg 2009, Shields et al 2014, deformation [Okumura et al 2010;Caricchi et al 2011, Ashwell et al 2015, crystal aggregation and crystal fragmentation [Pamukcu et al 2012], convection , Carey et al 2013] and development of permeability [Bai et al 2010, Degruyter et al 2010b, Bai et al 2011, Kendrick et al 2013, Ashwell et al 2015 in magma, which can be related to experiments, and which in the near future could feed into experimental and numerical modeling. Finally, information on fragmentation mechanisms (the terms "phreatic", "hydrothermal", and "hydromagmatic" are cause of great amount of discussion and debate about their meaning and use) can, in part, be assessed from particle morphology [Dellino et al 2012, Jordan et al 2014, Liu et al 2015b, while TGSD provide information on fragmentation efficiency [Kueppers et al 2006, Rust and Cashman 2011, Costa et al 2016.…”
Section: From Magma Ascentmentioning
confidence: 99%